Population, Employment and Poverty in the Rural Territories of Costa Rica (Revista Rupturas, 2018)
This paper examines the main characteristics of the rural population in Costa Rica in light of the National Household Survey (ENAHO 2017), paying attention to socioeconomic variables such as education, employment, income, migration and poverty. It also provides a series of elements and reflections related to the repositioning of rural territories in terms of governance and citizen action and the need to carry out a strategy to boost local and rural employment.
Keywords: Rural territory; employment; citizen; poverty; rural development